Implementation of Restorative Justice, The Intent of Punishment, and Legal Clarity In Indonesia - Fauziah Lubis; Fatimah Zahara; Wanda Hamidah (LPPM Universitas Ekasakti Padang, 2023)
This study looks at the fairness of restorative justice, the goal of punishment, and the need of legal certainty. According to the study's findings, restorative justice is still only being applied theoretically. In this instance, it emphasizes that the formalistic, long-established ideas of justice that have arisen in society and are applied in Indonesian customary law assemblies serve as the foundation for the genuine aim of sentencing. In contrast, the notions of individual deterrence and general deterrence call for actions to be absolute in order to produce a deterrent impact. Afterward, the idea of reform or rehabilitation was further developed. The use of restorative justice emphasizes the recovery of victims' material losses as a result of the perpetrators' unlawful acts, both physically and psychologically. This is done through a consensus-building process involving the perpetrator, the victim, the perpetrator's family, and the victim's family, as well as, if necessary, the community and the appropriate authorities. With relation to legal norms and values, this research methodology is normative juridical along with theories, legal doctrine, jurisprudence, applicable rules and regulations, as well as pubiications pertinent to the research topic. According to the study's findings, restorative justice is a noble form of justice when instances of illegal behavior have happened. Therefore, repair or restoration is crucial if the victim is to be rehabilitated or healed from the suffering he has endured on a material, physical, or psychic level. To be clear, restorative justice does not apply to all crimes; rather, it only does so in circumstances involving crimes against children, minor offenses, women in conflict with the law, and drug-related offenses. In order to provide clarity, there should be a firmness if the offender does not want to make restitution even though it is deemed capable of doing so in terms of material capabilities. There also needs to be concrete sanctions so that restorative justice is not only limited to other options; the legal framework for it should be expanded to the Constitution.